The Phonics Method in Aṣwat Learning and Its Influence on the Reading Ability of Ibtidaiyyah Madrasah Students - Irfan Hania; Muhammad Sya'dullah Fauzi; Suteja; Era Sastra Pangestu; Faiqotussana; Moh. Faza Rosyada (Jurusan Pendidikan Bahasa Arab UIN Sunan Kalijaga, 2022)
The application of traditional methods in learning Arabic is considered less successful, especially in introducing hijaiyyah letters, which results in stronger students' reading skills at the beginning level. The phonics method in Aṣwat learning is one of the many innovative language learning methods. A phonics method is a sound-based approach to teaching reading. This study aimed to see how much influence the phonics method had in teaching Aṣwat on students' reading skills at MIN Al-Muawanah Karawang. This research is an experimental one-group pretest-posttest design with the type of one-shot case study experiment. The research data were obtained from the pretest and posttest results, which who tested on a sample of 21 students at MIN Al-Muawanah Karawang. Data analysis and hypothesis testing used the normality test, one sample t-test, and paired sample t-test. The results of this study indicate that the difference in the average score of students before and after using the phonics method reached a difference of 55.89, where the initial, middle score was 7.22, and the average post-treatment score was 63.11. The difference in the mean scores was tested using a paired sample t-test with a significance value of 0.00 <0.05, which means that the use of the phonics method for nine fourth-grade students significantly affected students' beginning reading ability. Therefore, the results of this study can be used as an alternative to solving student problems in Aṣwat learning by educators, which has implications for increasing students' reading skills at the beginning level. Keywords: Phonic Method, Aṣwat, Student Ability, Reading Skills Abstrak Penerapan metode tradisional dalam pembelajaran bahasa Arab dianggap kurang berhasil, terutama materi pengenalan huruf-huruf hijaiyyah yang berakibat pada lemahnya kemampuan membaca siswa pada level permulaan. Metode fonik dalam pembelajaran Aṣwat merupakan satu dari sekian banyak inovasi metode pembelajaran lingusitik. Metode fonik merupakan metode dengan pendekatan berbasis suara untuk mengajar membaca. Tujuan dari penelitian ini adalah untuk melihat seberapa besar pengaruh metode fonik dalam pembelajaran Aṣwat terhadap kemampuan membaca siswa di MIN Al-Muawanah Karawang. Penelitian ini merupakan penelitian eksperimental one group pretest-porstest design dengan jenis ekperimen one-shot case study. Data penelitian diperoleh dari hasil pretest dan posttest yang diujikan pada sampel penelitian yang berjumlah 21 siswa MIN Al-Muawanah Karawang. Analisis data dan uji hipotesis menggunakan uji normalitas, uji t Satu Sampel, dan Uji T Sampel Berpasangan. perbedaan nilai rata-rata siswa sebelum dan sesudah menggunakan metode fonik mencapai selisisih sebesar 55,89, di mana rata-rata nilai awal sebesar 7,22, dan rata-rata nilai pasca treatment sebesar 63,11. Hasil penelitian ini menunjukkan bahwa perbedaan nilai rata-rata tersebut diuji menggunakan paired sample t-test dengan nilai signifikansi sebesar 0,00 < 0,05 yang berarti penggunaan metode fonik kepada 9 siswa kelas IV tersebut memiliki pengaruh yang signifikan dalam kemampuan membaca permulaan siswa. Oleh karena itu, dari hasil penelitian ini agar dapat dijadikan sebagai alternatif pemecahan masalah siswa dalam pembelajaran Aṣwat oleh para pendidik yang berimplikasi pada meningkatnya kemampuan membaca siswa pada level permulaan. Kata Kunci: Metode Fonik, Aṣwat, Kemampuan Siswa, Keterampilan Membaca